The execution of public works contract in South America under COVID-19: possible alternatives to maintain its economic balance or terminate it early - Wagemann Farfán, Alex (2020)
This paper studies the principal effects of COVID-19 in the execution of public works contracts throughout South America. In particular, different countries have declared that the construction of public infrastructure is an essential activity, a situation that has forced the contractors to fulfill their obligations in excessively onerous terms or outside the purpose that led to the termination of the agreements with the State Administration. Considering the above, this article analyzes the possible alternatives offered by the Law, either to reestablish the economic balance of the contract or to terminate the agreement early.